1995
DOI: 10.1111/j.1447-0756.1995.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Doppler Study of the Umbilical Artery in Predicting Perinatal Outcome in Pre‐Eclamptic Patients

Abstract: The abnormal Doppler result usually precedes the appearance of abnormal BPP. The abnormal Doppler result helps to identify the fetus at risk that needs further surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…The initial umbilical artery PI had good sensitivity for poor outcome and major morbidity (75 and 58% respectively) in line with other publications reporting more adverse outcome in pre-eclampsia when umbilical artery waveforms are abnormal. [11][12][13]18,19 The current results, however, are in contrast to 18 Yoon (1994), who showed the umbilical artery waveform to be an independent predictor of poor outcome with an odds ratio of 14.2 after correcting for GA. The much narrower definition of adverse outcome in the current, larger cohort, may account for the lower relative risk as well as the lack of statistical significance in multivariate analysis including the fetal weight estimation.…”
Section: Placental Insufficiencycontrasting
confidence: 98%
See 1 more Smart Citation
“…The initial umbilical artery PI had good sensitivity for poor outcome and major morbidity (75 and 58% respectively) in line with other publications reporting more adverse outcome in pre-eclampsia when umbilical artery waveforms are abnormal. [11][12][13]18,19 The current results, however, are in contrast to 18 Yoon (1994), who showed the umbilical artery waveform to be an independent predictor of poor outcome with an odds ratio of 14.2 after correcting for GA. The much narrower definition of adverse outcome in the current, larger cohort, may account for the lower relative risk as well as the lack of statistical significance in multivariate analysis including the fetal weight estimation.…”
Section: Placental Insufficiencycontrasting
confidence: 98%
“…2,5,6 The coexistence, temporal changes and prognostic implications of abnormal ultrasound and Doppler findings are now well described in placental insufficiency, [7][8][9] but while knowledge of umbilical artery Doppler results 10 is of clear clinical benefit, the use of other ultrasound and Doppler parameters has not yet been shown to improve perinatal outcome. In preterm pre-eclampsia, some studies have investigated the prognostic value of such parameters close to delivery, [11][12][13][14][15][16][17] but combinations of parameters, their inter-relations and the influence of confounding variables in this setting have not been investigated widely. [18][19][20] Before one can assume that assessment of fetoplacental blood flow patterns should affect the management of preterm pre-eclampsia, it needs to be established which findings contribute independently to the ultimate prognosis, either at the time of diagnosis or during serial reassessment.…”
Section: Introductionmentioning
confidence: 99%
“…The PPV for FGR reported in the individual studies were between 77.40 and 88.5,11 16 21 24 while the area under the receiver operating characteristic (AU ROC) curve was 0.63,17 mostly in high-risk pregnancies. The NPV ranged from 55.4 to 95.65 11 16 21 24. FGR was defined as birth weight or abdominal circumference below the 10th percentile in two studies,11 17 ponderal index less than 10 in one study,21 and was not defined in the remaining studies 16 24 26.…”
Section: Resultsmentioning
confidence: 97%
“…Twenty studies evaluated the UA,10–29 and seven reported its predictive values for FGR. The PPV for FGR reported in the individual studies were between 77.40 and 88.5,11 16 21 24 while the area under the receiver operating characteristic (AU ROC) curve was 0.63,17 mostly in high-risk pregnancies. The NPV ranged from 55.4 to 95.65 11 16 21 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation